Habilidades de coping em atletas escolares brasileiros - Renato Miranda; Danilo Reis Coimbra; Marcio Vidigal Miranda Junior; André Furiatti Russo; Alexandro Andrade; Maurício Bara Filho (Universidade Estadual do Oeste do Paraná, 2015)
The aim of this study was to analyze the coping skills in Brazilian school athletes, comparing male and female athletes and local and national level. The sample consisted of 105 school athletes of both (62.9% male) with age 16 ± 0.9 years and the practice time of 4.7 ± 2.5 years of team sports (volleyball, basketball, handball and futsal). Were 66 (62.9%) athletes of the National and 39 (37.1%) of the Local delegation. To evaluate the coping was used the questionnaire "Athletic Coping Skills Inventory-28BR." The Coping Total variable was analyzed separately using an ANOVA 2x2. The data of the specific skills of coping were analyzed using MANOVA two-factor "sex" and "competitive level" (National and Local) with scores of Coping with Adversity, Peak Performance Under Pressure, Mental Preparation/Goals, Concentration, Freedom for Worry, Motivation/Confidence and Trainability as dependent variables. Was no difference between male and female in Coping Total, Peak Performance Under Pressure, Mental Preparation/Goals, Concentration and Motivation/Confidence. Among the athletes National and Local performance was difference in the Peak Performance Under Pressure and Motivation/Confidence. Coaches and others involved in the context of school sports should pay attention to the development of these coping skills in their athletes, so that they improve performance and maximize the benefits that competitive sport can bring to young school athlete.